1972
DOI: 10.1126/science.177.4050.704
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Dichilorophenol, Sex Pheromone of the Lone Star Tick

Abstract: The compound 2,6-dichlorophenol was identified from female lone star ticks, Amblyomma americanum, and is believed to be a sex pheromone of this arthropod. The natural occurrence of a chlorinated organic compound in a land animal is new. The presence of similar compounds of exogenous origin is common in animals, but efforts to implicate an outside source for the halogenated phenol have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 3 publications
0
29
0
1
Order By: Relevance
“…Since the pioneer studies identifying 2,6-dichlorophenol (2,6-DCP) as an attractant sex pheromone in Amblyomma americanum (Linnaeus) (Berger et al 1971, Berger 1972 this same compound has been identified in 17 species of Ixodidae (Mayer & Mclanglin 1991, Bruyne & Guerin 1994, Liu et al 1998, Borges et al 2002. Although identified in several species, confirmatory studies showing its role as an attractant sex pheromone were conclusive in seven species: D. variabilis, Dermacentor Chow et al (1975) identified 2,6-DCP in R. sanguineus female extract and observed that males responded to this compound by waving their legs, and detaching from the host, but attraction to this compound was not confirmed.…”
mentioning
confidence: 99%
“…Since the pioneer studies identifying 2,6-dichlorophenol (2,6-DCP) as an attractant sex pheromone in Amblyomma americanum (Linnaeus) (Berger et al 1971, Berger 1972 this same compound has been identified in 17 species of Ixodidae (Mayer & Mclanglin 1991, Bruyne & Guerin 1994, Liu et al 1998, Borges et al 2002. Although identified in several species, confirmatory studies showing its role as an attractant sex pheromone were conclusive in seven species: D. variabilis, Dermacentor Chow et al (1975) identified 2,6-DCP in R. sanguineus female extract and observed that males responded to this compound by waving their legs, and detaching from the host, but attraction to this compound was not confirmed.…”
mentioning
confidence: 99%
“…Macroglumeruli have been described in the olfactory lobes of moths, cockroaches, and bees (ANTON & HOMBERG, 1999) and are believed to play a role in receiving information from olfactory receptor neurons that detect sex pheromones from distance. Ticks, including A. americanum, use sex pheromones to attract mates from short distances (BERGER, 1972). This may explain the lack of macroglomeruli in tick olfactory lobes.…”
Section: Discussionmentioning
confidence: 99%
“…americanum (Berger, 1972) and later shown to be produced by the foveal glands situated on the dorsal surface (Sonenshine et al, 1977). Whilst 2,6-DCP has now been identified in at least 5 genera, including 14 species, (Hamilton, 1992), Wood et al, (1975) were unable to find this compound in the four species of Rhipicephalus which they examined.…”
Section: Introductionmentioning
confidence: 97%